Single-Nucleus Transcriptomic Atlas of Human Pericoronary Epicardial Adipose Tissue in Normal and Pathological Conditions - Liu, Xuanyu; Yuan, Meng; Zhao, Danni; Zeng, Qingyi; Li, Wenke; Li, Tianjiao; Li, Qi; Zhuo, Yue; Luo, Mingyao; Chen, Pengfei; Wang, Liqing; Feng, Wei; et al. (Arteriosclerosis, thrombosis, and vascular biology, 2024)
BACKGROUND: Pericoronary epicardial adipose tissue (EAT) is a unique visceral fat depot that surrounds the adventitia of the coronary arteries without any anatomic barrier. Clinical studies have demonstrated the association between EAT volume and increased risks for coronary artery disease (CAD). However, the cellular and molecular mechanisms underlying the association remain elusive. METHODS: We performed single-nucleus RNA sequencing on pericoronary EAT samples collected from 3 groups of subjects: patients undergoing coronary bypass surgery for severe CAD (n=8), patients with CAD with concomitant type 2 diabetes (n=8), and patients with valvular diseases but without concomitant CAD and type 2 diabetes as the control group (n=8). Comparative analyses were performed among groups, including cellular compositional analysis, cell type-resolved transcriptomic changes, gene coexpression network analysis, and intercellular communication analysis. Immunofluorescence staining was performed to confirm the presence of CAD-associated subclusters. RESULTS: Unsupervised clustering of 73 386 nuclei identified 15 clusters, encompassing all known cell types in the adipose tissue. Distinct subpopulations were identified within primary cell types, including adipocytes, adipose stem and progenitor cells, and macrophages. CD83high macrophages and FOSBhigh adipocytes were significantly expanded in CAD. In comparison to normal controls, both disease groups exhibited dysregulated pathways and altered secretome in the primary cell types. Nevertheless, minimal differences were noted between the disease groups in terms of cellular composition and transcriptome. In addition, our data highlight a potential interplay between dysregulated circadian clock and altered physiological functions in adipocytes of pericoronary EAT. ANXA1 (annexin A1) and SEMA3B (semaphorin 3B) were identified as important adipokines potentially involved in functional changes of pericoronary EAT and CAD pathogenesis. CONCLUSIONS: We built a complete single-nucleus transcriptomic atlas of human pericoronary EAT in normal and diseased conditions of CAD. Our study lays the foundation for developing novel therapeutic strategies for treating CAD by targeting and modifying pericoronary EAT functions.